Assessment of the level of economies' foreign trade diversification - Oleksandr Popov; Sergiy Melnikov; Oleksandr Skachkov; Vasiliy Lyba (Contemporary Economics, 2022)
The aim of the study is to consider the concept of diversification in the context of foreign trade, to clarify the classification of types of foreign trade diversification, ways to assess the level and to conduct a mass assessment of the level of foreign trade diversification of countries. The justification of the undertaken topic is that the national economies of the modern world do not function autonomously, they are interconnected by trade, co-production, financial and migration flows, and following international integration, these relationships are only strengthening. Therefore, the disruption of foreign trade relations of countries can cause more problems, lower the level of their foreign trade diversification. However, despite of these, today the issue of foreign trade diversification is not sufficiently deeply studied, including ways to classify foreign trade diversification and assess its level. The research methodology includes methods for calculating indicators characterizing the level of diversification. For calculations, the values of indicators characterizing the annual volume of international trade of the countries of the world are used. The results of calculation of indicators of the level of foreign trade diversification according to statistical data on the volume of imports and exports of the world are presented. Choropleth maps of the level of foreign trade diversification of the world are created. Conclusions are made on the possibility and convenience of using indicators of foreign trade diversification.
Keywords: F14; F43; O11; 330; diversification; foreign trade; commodity diversification; geographical diversification